2023
DOI: 10.1002/jsfa.12781
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of Bacillus licheniformis against inflammatory responses and intestinal barrier damage in broilers with necrotic enteritis induced by Clostridium perfringens

Abstract: BackgroundBacillus licheniformis is a gram‐positive bacterium that has strong environmental adaptability and can improve the growth performance, immunity, and antioxidant function of broilers. The current study aimed to elucidate the protective capability of B. licheniformis against inflammatory responses and intestinal barrier damage in broilers with necrotic enteritis (NE) induced by Clostridium perfringens (CP).ResultsThe results showed that B. licheniformis enhanced the final body weight in broilers compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…In the present study, serum D-LA and DAO concentrations were higher in broiler chickens with NE, suggesting that NE impairs intestinal barrier integrity. This is consistent with the results of a previous study [23,46,47]. The decline in serum D-LA and DAO concentrations observed in broilers after the addition of tannic acid, indicating the potential positive impact of tannic acid on maintaining intestinal barrier integrity in broilers with NE.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, serum D-LA and DAO concentrations were higher in broiler chickens with NE, suggesting that NE impairs intestinal barrier integrity. This is consistent with the results of a previous study [23,46,47]. The decline in serum D-LA and DAO concentrations observed in broilers after the addition of tannic acid, indicating the potential positive impact of tannic acid on maintaining intestinal barrier integrity in broilers with NE.…”
Section: Discussionsupporting
confidence: 92%
“…Immunoglobulins are synthesized and secreted by B-cells after immune cells are activated by antigens, which can bind to specific antigens in order to defend against invading pathogens [25]. In this study, the results showed that C. perfringens infection decreased the immunoglobulin levels in sera, while SB and MS-SB improved the secretion of immunoglobulins, consistent with the results of previous studies [26]. However, it should be noted that the enhancement brought by SB and MS-SB was diminished under C. perfringens infection, when compared to normal conditions.…”
Section: Discussionsupporting
confidence: 91%